Implementasi Teorema Bayes Untuk Diagnosa Penyakit Hawar Daun Bakteri (Kresek) Dan Penyakit Blas Tanaman Padi - Purwadi Purwadi; Asyahri Hadi Nasyuha (JURIKOM (Jurnal Riset Komputer), 2022)
Rice is a plant that has an important role for the majority of the population in Indonesia. Rice plants have a fairly high carbohydrate content. Therefore, rice cultivation is very important to be maintained. The government is targeting rice yields in 2013 to reach 72.06 million tons of dry milled grains and a surplus of 10 million tons in 2015. But in fact, this has not been realized due to disease attacks on rice plants which are quite detrimental to farmers. This is due to the lack of knowledge among Indonesian farmers about the problem of rice plant diseases. Farmers often have difficulty in consulting with an expert because of the travel time to the agricultural office which is quite far. In this expert system research, the Bayes theorem calculation method determines the probability of an event based on the effects obtained through observations. The result of the analysis of this method is an expert system analysis to diagnose diseases in rice plants along with the probability value of the diagnosed disease, which shows the level of system confidence in the disease by Bayes calculation that the conclusion with the highest value of 0.574 is Blast Disease